Evaluasi User Experience Aplikasi Coop Access Dengan Menggunakan Metode User Experience Questionnaire - Riordan Jaka Rachmadi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to evaluate the user experience of Coop Access application users at Financial Cooperatives. This research is quantitative research. The method used to obtain primary data was to use a survey, then the data was processed using Data Analysis Tool Version 11. The population studied in this research were members of Koperasi Wanita Sejahtera who were users of the Coop Access application and numbered 166 subjects. Using the Slovin’s formula, the number of samples used in this research was 117. The user experience dimension was divided into six indicators, namely attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The results of descriptive statistical analysis show varied evaluation results for each dimension. The evaluation results for the attractiveness, perspicuity and efficiency dimensions obtained good evaluation results, while the stimulation and novelty dimensions received above average evaluation results. What needs to be of primary concern is the dependability dimension because this dimension has below average evaluation results. The conclusion obtained from this research is that the Coop Access application is an application that is considered to provide a good user experience but is still not reliable yet.